Pizarnik y el cine: películas parisinas de 1960-1964 en sus Diarios - Santiago Hamelau (Cuadernos LIRICO, 2023)
The article intends to analyse the relationship between Pizarnik and the cinema recorded in her diary during the Parisian years. Our interest is to demonstrate that Pizarnik's audiovisual conversation is born from a utopian asymmetry, since the films stir up desire and allow the self to want to be what it is not. At the opposite pole, the external world and the body will pin the voice to the present, driving her away from the utopian place while increasing the gravitational force of the ideal.